ANALISIS KINERJA PEMASARAN PT ALFA SCORPII MEDAN - Aulia Arief Nasution (Jurnal Riset AKuntansi dan Bisnis, 2014)
Topic this research is Market Orientation, Product Completeness and Effectiveness of Distribution Channel Marketing significant effect on performance in PT. Alpha Scorpii of Medan. The population of this study are all employees of PT. Alpha Scorpii of Medan. Where samples were taken in this study were as many as 50 people. Data was collected using questionnaires and observation. Data were tested by using test validity and reliability, data must also satisfy Assumption Test Classic. Further analysis of test data by using multiple regression analysis, t test, F test and the coefficient of determination. This study concluded that the partial test results and simultaneously, Market Orientation, Product Completeness and Effectiveness of Distribution Channel Marketing significant effect on performance. Effectiveness of distribution channels is more dominant effect on performance. Ability Market Orientation, Product Completeness and Effectiveness of Distribution Channel Marketing in explaining performance is at 43.4% while the remaining 56.6% is explained by other factors not included in this research model.